Absence of renal protection of an aqueous extract of the Costa Rican plant Calzoncillo (Passiflora biflora), using a model of acute kidney injury (AKI) in female Wistar rat - Zamora Murillo, Edson (2020)
In Costa Rica, the use of medicinal plants is a common practice; this is the case of Passiflora biflora, often known as Calzoncillo, which has been used to treat conditions associated with renal function. However, the background of safety and efficacy of the use of this plant is very limited and practically non-existent regarding its renal effect. This work aimed to evaluate the existence of protection at the renal level of an aqueous extract of Calzoncillo employing a model of acute kidney injury (AKI) in female Wistar rats. The extract was prepared and characterized by a basic phytochemical screening. A biological test was carried out for which 4 groups were formed: no AKI (negative control), AKI (positive control), AKI plus pretreatment and AKI plus treatment. AKI was induced by administering a single dose of 20 mg/kg of potassium chromate. Some biomarkers of renal function were determined by measuring serum and urinary creatinine, glucose, sodium, and potassium levels; also, the urinary concentration of creatinine, glucose, sodium, potassium, and protein was determined. Finally, a histopathological study of the kidneys was performed. A significant decrease in creatinine clearance and urinary sodium excretion in the AKI groups compared to control was observed. Additionally, the urinary excretion of proteins and glucose, as well as the urinary excretion of potassium showed a significant increase in the groups with AKI compared to the negative control. Histopathological analyses revealed the presence of pyknotic nuclei, hyaline deposits, loss of microvilli and other signs of kidney damage in the groups with AKI. These results allowed us to conclude that the aqueous extract of Costa Rican Passiflora biflora has no nephroprotective effect at the used dose.